Application of coolants during tool-based machining – A review - Yang, Khor Zheng; Pramanik, Alokesh; Basak, A.K.; Dong, Roger; Prakash, Chander; Shankar, S.; Dixit, Saurav; Kumar, Kaushal; Vatin, Nikolai Ivanovich (Ain Shams University, 2023)
Coolant is a substance that applied in a machining process for the efficient machining of materials. The application of coolants is based on the several factors including the types of machining process, workpiece material, cutting tool and cost. Coolant helps to dissipate the heat that can be generated during the machining operation, induce lubricating effects to decrease the friction caused by the interfaces of two surfaces, flush away chips and offer corrosion protection. With the right type of coolants used, the performance of machining applications and the attributes of workpieces can be remarkably enhanced. The objective of the study to provides a critical review on the mechanism of coolant penetration, functions, variety of coolants, cooling actions, effectiveness, applications, and the additives that alter the ability and properties of coolants. Furthermore, the critical review also addresses the new technology cryogenic machining that uses cryogenic gases as coolants instead of conventional coolants.